Applying Two Stay Two Stray Technique in Improving the Students’ Reading Comprehension - Siti Hardiyanti Bahnar; Rahmi Rais (ELT Worldwide: Journal of English Language Teaching, 2022)
This study investigates the effect of the Two Stay Two Stray (TSTS) Technique on the reading comprehension of report texts by eleventh-grade SMAN 1 Barru students. In this study, there are two problem statements: 1)Is the Two-Stay Two-Stray strategy beneficial in enhancing the reading comprehension of report material among eleventh-grade students of SMA Negeri 1 Barru? And 2) Are the students enthusiastic about reading instruction utilizing the TSTS Technique?. This study utilized a quasi-experimental approach with one pre-test and one post-test for each of two classes. The sample was obtained from the population using a cluster random sampling technique. Teachers typically employ a standard style and technique when instructing their students. Two Stay Two Stray is a teaching strategy that can be implemented by teachers in reading classes as a result of this study. The outcome of the posttest suggested that there was a significant difference in the comprehension achievement of students before and after reading instruction utilizing the TSTS Technique. The study discovered, based on their study of the data, that the Two Stay Two Stray Technique could enhance students' reading comprehension.